Epithelial expression in high grade sarcomas / Siti Aishah Mahamad Dom - Siti Aishah, Mahamad Dom (2017)
High grade sarcomas are a heterogeneous group of sarcomas often lacking defining cytomorphological or immunohistochemical evidence of specific lineage differentiation. Many of these tumours previously know as Malignant fibrous histiocytoma (MFH) are currently redefined in the WHO 2013 classification of tumours of soft tissue and bone as Undifferentiated or Unclassified hight grade sarcomas or Undifferentiated pleomorphic sarcomas (UPS). In some series expression of epithelial markers in high grade sarcomas were recorded. A retrospective study of a cohort of high grade sarcomas which include UPS cases as well as other more specific high grade sarcomas eg Synovial sarcoma and Epithelioid sarcoma and high grade but lineage specific sarcomas eg high grade Malignant peripheral nerve sheath tumour (MPNST) seen at the University Malaya Medical Centre over an eleven-year period was undertaken to study the frequency and extent of epithelial expression of Cytokeratin and Epithelial membrane antigen (EMA). The clinicopathological features of these cases were also evaluated for any correlation. lmmunohistochemical staining for epithelial expressions of cytokeratin - MNF116 and AE1/AE3 and EMA were evaluated in 100 resected specimens of high grade sarcoma cases. Epithelial expression was seen in 32 (32%) of the 100 cases evaluated either as single marker or multiple marker expression. Cytokeratin was expressed in 12 cases (10 MNF116 and 2 AE1/E3 - positive cases) and EMA was expressed in 26 cases in variable extents of focal, intermediate or diffuse patterns. The figures include the overlap of cases expressing 1 or more than 1 marker. There was a significant association between specific epithelial markers and histological type of tumour and patient gender. There was no significant association of these epithelial markers with the following parameters: patient age and tumour size, location and origin with reference to primary, recurrent and metastatic tumours. Our study highlights the evidence of epithelial differentiation in high grade sarcomas and the diagnostic, therapeutic and prognostic implications. Key words: high grade sarcoma, epithelial differentiation, cytokeratin, EMA.